Does extra feed affect breeding affect litter size? - Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fertility was evaluated in sows fed 4 vs 10 lb/d and gilts fed 4 vs 7.4 Ibid during the first 10 days after breeding. No effects on farrowing rate or litter traits were detected. This confirms results of a previous KSU experiment. Therefore, high feed intake after breeding may not affect fertility traits.
Keywords: Swine; Sows; Intake; Reproductive performance; Gestation